1999
DOI: 10.1073/pnas.96.14.7968
|View full text |Cite
|
Sign up to set email alerts
|

p200 ARF–GEP1: A Golgi-localized guanine nucleotide exchange protein whose Sec7 domain is targeted by the drug brefeldin A

Abstract: The drug brefeldin A (BFA) disrupts protein traffic and Golgi morphology by blocking activation of ADP ribosylation factors (ARFs) through an unknown mechanism. Here, we investigated the cellular localization and BFA sensitivity of human p200 ARF-GEP1 (p200), a ubiquitously expressed guanine nucleotide exchange factor of the Sec7 domain family. Multiple tagged forms of the full-length polypeptide localized to tight ribbon-like perinuclear structures that overlapped with the Golgi marker mannosidase II and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 26 publications
3
105
1
1
Order By: Relevance
“…29,36 Unlike in cytohesins, this extended PH domain is not autoinhibitory. 29,46 The crystal structure of a human BRAG2 construct comprising the Sec7 and PH domains in complex with Arf showed that the PH domain forms extensive intramolecular interactions with the Sec7 domain.…”
Section: Regulation Of Ph Domain-containing Arfgefs By Membranesmentioning
confidence: 99%
“…29,36 Unlike in cytohesins, this extended PH domain is not autoinhibitory. 29,46 The crystal structure of a human BRAG2 construct comprising the Sec7 and PH domains in complex with Arf showed that the PH domain forms extensive intramolecular interactions with the Sec7 domain.…”
Section: Regulation Of Ph Domain-containing Arfgefs By Membranesmentioning
confidence: 99%
“…BFA inhibits activation of Arf1 (a key player in vesicle formation) by targeting its activators, the GEFs GBF1 and BIG1/2 (Claude et al 1999;Mansour et al 1999;Yamaji et al 2000;Kawamoto et al 2002), which are localized to the cis-and trans-Golgi, respectively, and have distinct functions at the Golgi (Manolea et al 2008). Recent studies reveal that Chlamydia uses GBF1 (but not BIG1/2) to acquire sphingomyelin, which is necessary for inclusion membrane growth and stability but not bacterial replication (Elwell et al 2011).…”
Section: Interactions With Host-cell Organelles For Acquisition Of Homentioning
confidence: 99%
“…After digestion with KpnI and XbaI the fragment was subcloned into the KpnI and XbaI sites of the plasmid pcDNA3 (Invitrogen). Cells were transfected using the FuGENE 6 reagent following the procedure described by Mansour et al 63 using the pcDNA3 containing the GCBHP2 in transcriptional orientation. As a control, mock-transfection was performed with the pcDNA3 without the GCBHP2 insert.…”
Section: Hek-293mentioning
confidence: 99%